Analisis Yuridis Ketentuan Hukum yang Hidup dalam Masyarakat pada Kitab Undang-Undang Hukum Pidana Indonesia - Irawan, Ade; Pura, Margo Hadi (Ajudikasi : Jurnal Ilmu Hukum, 2023)
The research on "Juridical Analysis of Provisions Regarding Living Laws in the Community in the National Criminal Code" is motivated by the emergence of the issue of including provisions regarding living law in the National Criminal Code. This study aims to explore the position of customary law in Indonesian positive law and to analyze in depth the existing legal arrangements in the Criminal Code. This study uses a normative-conceptual legal research method, focusing on laws and norms that apply in society and collecting data through library research. After conducting research, the results show that the recognition of customary law community units has been contained in the 1945 Constitution of the Republic of Indonesia, which at the same time recognizes applicable customary law, but the Criminal Code, which was adopted from the Netherlands, has not contained rules regarding customary law; only the National Criminal Code contains provisions regarding living law as an extension of the principle of legality, accompanied by sanctions, and the method of application, which, in the dynamics of society, still raises pros and cons. For this reason, the state must also provide the best legal certainty regarding this matter, including being willing to accept all forms of aspirations from the community and being willing to review the National Criminal Code if there is a request for review at the Constitutional Court.